2011
DOI: 10.1093/chemse/bjr108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of "Rose Essential Oil" Inhalation on Stress-Induced Skin-Barrier Disruption in Rats and Humans

Abstract: In stressed animals, several brain regions (e.g., hypothalamic paraventricular nucleus [PVN]) exhibit neuronal activation, which increases plasma adrenocorticotropic hormone (ACTH) and glucocorticoids. We previously reported that so-called "green odor" inhibits stress-induced activation of the hypothalamo-pituitary-adrenocortical axis (HPA axis) and thereby prevents the chronic stress-induced disruption of the skin barrier. Here, we investigated whether rose essential oil, another sedative odorant, inhibits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 24 publications
3
35
1
1
Order By: Relevance
“…7) In the present study, we could not obtain recovery of ratios of weights of the adrenal glands and thymus relative to the body weight of stress-HEO rats (Fig. 2).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…7) In the present study, we could not obtain recovery of ratios of weights of the adrenal glands and thymus relative to the body weight of stress-HEO rats (Fig. 2).…”
Section: Discussioncontrasting
confidence: 59%
“…Fukada et al (2012) revealed that the inhalation of rose essential oil significantly inhibits an increase in stress hormones in restraint stressed rats. 7) The study by Carvalho-Freitas and Costa (2002) on the treatment of mice with orange oil also revealed that this oil could be useful as an antianxiety agent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhalation of odorants, which have a sedative effect, accelerates skin barrier recovery in humans [2]. Chronic stress-induced disruption of the skin barrier can be limited or prevented by rose essential oil inhalation [55].…”
Section: Classification Endpointmentioning
confidence: 99%
“…Physiological/psychological effects of rose aromas have been reported; a sedative effect by decreasing sympathetic nerve activity (Haze et al, 2002), prevention of skin barrier disruption (Fukada et al, 2012), anxiolytic effects (Bradley et al, 2007), and an anticonflict effect (Umezu et al, 2002). Many of these reports focused on the effect of rose essential oils, but the effect of fresh rose flowers on humans has not sufficiently reported.…”
Section: Introductionmentioning
confidence: 99%